Perancangan Interior Restaurant Library Dessert Island di Surabaya - Shierly Angelita; Stephanus Pantja Honggowidjaja; Mohammad Taufan Rizqy (Intra, 2019)
Restaurant library is a place where people are willing to spend their time to eat, drink, read, and even to share stories with their relatives. The existence of restaurant library is not just for enjoying food, but also educating them by adding insight through the books collection about traveling and culinary. In order to achieve the purpose of this restaurant library, “Dessert Island” concept is applied. Within this concept, the ideas of transitional furniture and interior element combine the feminism and masculine using natural materials. A warm ambience which comforts people inside this restaurant library will certainly make them do anything even far better. The facilities in the restaurant library must be adjusted to the people’s needs by dividing restaurant library to few areas so people can move comfortably. This design plan is expected to succeed giving positive impacts to people inside this restaurant library.